Factors associated with the mental suffering of undergraduate students in São Paulo from 2017 to 2021 - Fabricio Gobetti Leonardi; Rosemarie Andreazza; Gabriela Arantes Wagner (Avaliação: Revista da Avaliação da Educação Superior)
Abstract The mental suffering among university students impacts academic life and student retention. Especially during the COVID-19 pandemic, mental health was a sensitive topic with in university communities, prompting the development of institutional strategies. In this context, the objective of this study was to identify and compare the factors associated with the mental suffering of undergraduate students at the Federal University of São Paulo (Unifesp) in the period of 2017-2019 (pre-COVID-19 pandemic) and 2020-2021 (during the COVID-19 pandemic). This is a cross-sectional study based on the analysis of secondary data from 14,092 undergraduate students between 2017-2021, obtained by the Study Commission on the Profile of Undergraduate Students at Unifesp between 2017-2021. The data showed important associations regarding the mental health of these students, highlighting an increased likelihood of mental suffering among more vulnerable groups (people with disabilities, women, travestis/transgender individuals). Engaging in physical activity sporadically or regularly served as a protective factor in both analyzed periods. The findings show an increase in mental suffering among students, including the use of psychotropic drugs during the COVID-19 pandemic. It is recommended that student retention policies be developed from the moment students enter higher education, incorporating strategies aimed at students experiencing mental suffering, especially women, transgender students, people with disabilities, and workers.